Investigating Alternative Container Formats for Lyophilization of Biological Materials Using Diphtheria Antitoxin Monoclonal Antibody as a Model Molecule - Kiran P. Malik; Chinwe Duru; Paul Stickings; Esther Veronika Wenzel; Michael Hust; Paul Matejtschuk (MDPI AG, 2021)
When preparing biological reference materials, the stability of the lyophilized product is critical for long-term storage, particularly in order to meet WHO International Standards, which are not assigned expiry dates but are expected to be in use for several decades. Glass ampoules are typically used by the National Institute for Biological Standards and Control (NIBSC) for the lyophilization of biological materials. More recently, a clear need has arisen for the filling of smaller volumes, for which ampoules may not be optimal. We investigated the use of plastic microtubes as an alternative container for small volume fills. In this study, a recombinant diphtheria antitoxin monoclonal antibody (DATMAB) was used as a model molecule to investigate the suitability of plastic microtubes for filling small volumes. The stability and quality of the dried material was assessed after an accelerated degradation study using a toxin neutralization test and size exclusion HPLC. While microtubes have shown some promise in the past for use in the lyophilization of some biological materials, issues with stability may arise when more labile materials are freeze-dried. We demonstrate here that the microtube format is unsuitable for ensuring the stability of this monoclonal antibody.